2011
DOI: 10.1007/s10086-011-1235-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of color changes in cellulose during heat treatment

Abstract: This paper deals with the kinetics of the color changes of cellulose during heat treatment. The color of cellulose heated at 90-180°C was measured by a spectrophotometer and expressed by CIELAB color parameters. The values of L* decreased and those of a*, b* and DE* ab increased at all the treatment temperatures. Several kinetic models, namely, the zero-order, first-order, second-order and autocatalytic model, were applied to the changes in the color values. Furthermore, the results of kinetic analysis using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 31 publications
(39 reference statements)
2
23
0
1
Order By: Relevance
“…It was reported that the changes in L * and DE * of hinoki had similar degree to those of cellulose during heat treatment at 180°C. Carbonyl groups in the cellulose chains and the formation of low molecular substances (furan type) were estimated as being responsible for the colour changes [21]. Moreover, total changes of colour in thermally modified wood originates from chemical changes more in lignin than in polysaccharides, due to the darkening of lignin itself, which is associated with the generation of chromophoric groups [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the changes in L * and DE * of hinoki had similar degree to those of cellulose during heat treatment at 180°C. Carbonyl groups in the cellulose chains and the formation of low molecular substances (furan type) were estimated as being responsible for the colour changes [21]. Moreover, total changes of colour in thermally modified wood originates from chemical changes more in lignin than in polysaccharides, due to the darkening of lignin itself, which is associated with the generation of chromophoric groups [18].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies performed on solid wood have investigated the changes in wood colour that appeared during heat treatment and imply alteration of wood components [17][18][19]. The colour that wood gets after heat treatment was suggested to be an indicator of the degree of its modification and also a direct indication of chemical changes [20,21]. Little information addressed the veneers modification of various wood species by heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The TTSP was originally used to analyze material viscoelasticity [25], and it is widely used to analyze the mechanical properties of wood [26], such as wood creep performance [27][28][29]. The TTSP was also used in thermal degradation analysis combined with the Arrhenius equation, and it has been used for the determination of the color change of cellulose [30] and wood-plastic composite discoloration analysis [31]. In recent years, model-building methods have also been used in the field of wood thermal discoloration for further examination and experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…As the second parameter, the pre-dry temperature was tested by 30, 60 and 90 °C with the chosen spinning speed of 1700 cm/min. Above 100 °C, the CNFs in the suspension began denaturation with color change thus the temperature was changed below 100 °C [28]. In this experiment, the case of 30 °C reveals the highest mechanical properties.…”
Section: Resultsmentioning
confidence: 76%